2014
DOI: 10.1111/jopy.12103
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Meaning in Life, Social and Achievement Events, and Positive and Negative Affect in Daily Life

Abstract: Research on meaning in life has generally focused on global meaning judgments. This study examined how people's daily experiences, represented by events that occur in daily life, influence their perceived sense of meaning on a daily basis. One hundred sixty-two college students completed daily reports for 2 weeks. We examined the relationships among daily social and achievement events, daily positive and negative affect, and daily meaning in life. In addition, we tested the possible moderating influence of dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 67 publications
4
64
0
Order By: Relevance
“…In addition to the relationships between presence and search, we examined the relationships between each construct and several well‐being indicators. The relationships between presence and well‐being were positive at both the between‐ and within‐person relationships, which is consistent with previous research (e.g., King et al, ; Machell et al, ; Steger et al, ). In contrast, searching for MIL was negatively related to well‐being at the between‐person level, which is also consistent with previous research.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to the relationships between presence and search, we examined the relationships between each construct and several well‐being indicators. The relationships between presence and well‐being were positive at both the between‐ and within‐person relationships, which is consistent with previous research (e.g., King et al, ; Machell et al, ; Steger et al, ). In contrast, searching for MIL was negatively related to well‐being at the between‐person level, which is also consistent with previous research.…”
Section: Discussionsupporting
confidence: 91%
“…Regardless, similar to the results of trait‐level studies, presence of MIL and well‐being have been found to be positively related at the within‐person level. Daily presence of MIL has been found to be positively related to daily positive affect and negatively related to negative affect (King et al, ; Machell, Kashdan, Short, & Nezlek, ). Daily presence of MIL was also found to be positively related to a measure of subjective well‐being that consisted of a combination of daily life satisfaction and affect balance (positive affect minus negative affect) (Steger & Frazier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Daily measures of MIL, PA, and FTF were created based on items from the pre‐post assessment measures to assess state levels of these variables on the specific days when the participants filled out the daily surveys. To reduce the burden of repeated responses inherent in diary studies, only items with high face validity or high loadings in an exploratory factor analysis were selected for each variable (Machell, Kashdan, Short, & Nezlek, ; Xanthopoulou, Bakker, Demerouti, & Schaufeli, ). Similar to Steger et al (), participants responded to each item on a separate rating scale ranging from 0 ( not at all ) to 100 ( absolutely ).…”
Section: Methodsmentioning
confidence: 99%
“…Positive events occur frequently in people's life (Gable, Reis, Impett, & Asher, ) and are associated with higher relationship satisfaction in couples (Gable et al., ). Positive events also contribute to increased responsiveness from others, increased trust, and have a positive influence on people who are depressed (Machell, Kashdan, Short, & Nezlek, ; Nezlek & Gable, ; Reis et al., ). Furthermore, specific types of positive events such as expressing gratitude (Gordon, Impett, Kogan, Oveis, & Keltner, ; Williams & Bartlett, ), forgiving (Fincham, Hall, & Beach, ; Gordon, Hughes, Tomcik, Dixon, & Litzinger, ), expressing affection or intimacy (Debrot, Cook, Perrez, & Horn, ; Laurenceau, Barrett, & Rovine, ), and spending time together (Anderson, Van Ryzin, & Doherty, ) are positively related to relationship satisfaction.…”
Section: Introductionmentioning
confidence: 99%